The Transformation of Byod Practices to Support Green Computing in Malaysia Public Sector - Yusri Jusoh, Mohd; Haron, Haryani; Kaur, Jasber (International Journal of Engineering and Technology, 2018)
Bring your own Device (BYOD) is currently heightened as an approach towards green computing. With the current usage of mobile devices such as the smart phones, tablets, and laptops as the necessity in the working environment, the concept of BYOD went beyond personal use towards workplace. This study explores the BYOD practices and the contributions to support green computing in Malaysia public sector. Theoretical in this study were tested through a study in selected ministry in Malaysia. Qualitative research approach is used in the study with the main data collection method of interviews and document analysis. The study discovered two models of BYOD approach in the Malaysian public sector, which are the personally owned devices model and the organization owned devices model. This study concludes that both models can support green computing in Malaysia public sector; however no policy related to processes procedure of BYOD that can be used as guideline for green IT practices.Â Â